A Pragmatic Study of Speech Acts in Poor Things (2023) Movie - Syahrani Sam; Muhammad Hasbi (PT. Global Research Collaboration, 2025)
This study explores the types and functions of speech acts employed by characters in Poor Things (2023), a film rich in philosophical, emotional, and ideological discourse. Drawing upon Yule’s classification of speech acts; declarative, representative, expressive, directive, and commissive, this research applies a descriptive qualitative approach to analyze 242 selected utterances from the movie’s script. The data were collected through careful viewing, transcription, and contextual interpretation of the dialogues. Findings reveal that representative speech acts dominate the film, indicating characters' tendencies to express beliefs and shape perceptions. Expressive and directive acts also occur frequently, reflecting the emotional depth and interpersonal influence present in the narrative. Notably, declarative acts, though rare, serve pivotal roles in reshaping social realities and character relationships. These patterns underscore how speech act theory can illuminate character development and thematic construction in cinematic dialogue. This study contributes to the field of pragmatics and film discourse analysis by demonstrating how language functions not merely as communication, but as a tool of agency, identity formation, and narrative progression in contemporary cinema.